Is Consanguinity an Impediment to Improving Human Development Outcomes? - Mete, Cem (World Bank, Washington, DC, 2017)
This paper uses unique data collected in rural Pakistan to assess the extent to which consanguinity, which is widespread in North Africa, Central and West Asia, and most parts of South Asia, is linked to child cognitive ability and nutritional status. As economic benefits of marrying cousins may lead to upward bias in estimates of the effects of consanguinity on child outcomes, prior work likely underestimates the negative impacts of consanguinity on child outcomes. This paper finds that children born into consanguineous marriages have lower test scores, lower height-for-age, and a higher likelihood of being severely stunted. After controlling for current household wealth and parent education, the effects of endogenous consanguinity on child cognitive ability and height-for-age are identified by (current and past) grandfather land ownership and maternal grandparent mortality as instruments for consanguineous marriage of parents.